Peningkatan Kemampuan Mahasiswa dalam Manajemen Usaha, Produksi dan Operasi melalui Kunjungan Industri PT. XYZ - Fadli Agus Triansyah; Andi Cici Thania; Marito Ritonga; Nela Permata Sari Lubis; Sakina Balqis; Nabila Tijani Tharifah; Al Wahfi Suhada Sipahutar; Muh Ainul Yaqin; Hafiz Irwandi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to enhance students’ competencies in business management, production, and operations through an industrial visit to PT. XYZ. The activity involved 65 students from the Entrepreneurship Study Program of Universitas Negeri Medan and was conducted in December 2025. The method used was experiential learning, allowing students to gain direct exposure to real industrial practices. The stages of the activity included preparation, implementation of the industrial visit, observation and data analysis, and evaluation and reflection. The results of the activity indicate significant improvements in five key areas: understanding of business management, production processes, operations management, development of soft skills, and increased entrepreneurial motivation and interest. Students were able to connect theoretical knowledge with real-world applications, thereby enhancing their analytical and practical abilities. In addition, the activity contributed to the development of communication skills, teamwork, critical thinking, and professional attitudes. Overall, this program demonstrates that industrial visits are an effective learning strategy in entrepreneurship education to produce competent, adaptive, and competitive graduates.